2007
DOI: 10.1007/s11664-006-0033-0
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Soldered Joints Formed under Microgravity Conditions

Abstract: Experiments have been carried out to compare the mechanical strength of joints soldered with Sn-Ag-Cu under different gravitational conditions. Joints soldered under microgravity (produced during a parabolic flight) have lower strength (by 32% in this case) than similar joints formed under normal gravity. Electron microscopy has shown that this is due to a larger volume of residual porosity (14%) in the joints formed in microgravity compared with <1% for joints formed in normal gravity. The residual porosity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Imperial College London flew an experiment onboard a parabolic aircraft flight designed to test the strength of microgravity solder joints made under microgravity conditions. This experiment found that interior porosity of joints increased from 1% to 14% and that the strength of the connection decreased by 32% for joints formed during the flight as compared to those formed under normal gravity conditions [7].…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…Imperial College London flew an experiment onboard a parabolic aircraft flight designed to test the strength of microgravity solder joints made under microgravity conditions. This experiment found that interior porosity of joints increased from 1% to 14% and that the strength of the connection decreased by 32% for joints formed during the flight as compared to those formed under normal gravity conditions [7].…”
Section: Literature Reviewmentioning
confidence: 90%
“…The joined copper plates can be inserted into an Arcan disc [25], so that both the shear and tensile strength can be tested using an available tensile testing machine (see Figure 32). A test of this nature was previously performed by Imperial College London [7] to quantify the reduction of strength of microgravity solder joints. WVU's MRT conducted a similar experiment on its most recent flight to verify these results and compare strength data for solder joints using the magnetic solder paste to those formed under nonmagnetic conditions, both in microgravity and normal gravity environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation